THE EFFECTIVENESS OF ENVIRONMENTAL CAMPAIGNS IN SOCIAL MEDIA ON PEOPLE'S BEHAVIOUR CHANGE - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
Environmental campaigns on social media have become an increasingly popular tool to promote changes in people's behaviour towards a more environmentally friendly lifestyle. This research aims to evaluate the effectiveness of such campaigns in influencing people's behaviour change. The study in this research uses the literature method. The results show that environmental campaigns on social media have significant potential to raise public awareness and drive short-term behaviour change. However, to achieve sustainable behaviour change, these campaigns must be part of a more holistic strategy, involve collaboration with various stakeholders, and be supported by relevant policies and initiatives. This study provides important insights into the role of social media campaigns in addressing environmental challenges and highlights the need for an integrated approach to achieve lasting behaviour change in society.